ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN MODAL INTELEKTUAL (Studi Empiris pada Perusahaan yang Terdaftar di “Indeks Kompas 100” Tahun 2010-2012) - Adi Putra Setianto; Agus Purwanto (Diponegoro Journal of Accounting, 2014)
This research aims to analyze the influence of firm size, ownership concentration, leverage, profitability, auditor type, level of intellectual capital, and listing status on the intellectual capital disclosure. This research is using industry affiliation as control variabel. The populations of this research are all companies that listed in Indeks Kompas 100 Indonesian Stock Exchange (IDX) during 2010-2012. The sample was selected using purposive sampling method and obtained fourty eight companies being sampled. This research analyzes the company’s annual report using the method of content analysis. Data analysis used descriptive statistics, classical assumption test, and multiple linear regression analysis. The result of this study showed that firm size, ownership concentration, auditor type and listing status significantly influence to the intellectual capital disclosure. Meanwhile, leverage, profitability, and level of intellectual capital had no effect to the intellectual capital disclosure.